2017
DOI: 10.1007/s00500-016-2470-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting dynamic transaction queue size in scalable memory systems

Abstract: In order to increase parallelism via memory width in scalable memory systems, a straightforward approach is to employ larger number of memory controllers (MCs). Nevertheless, a number of researches have pointed out that, even executing bandwidth-bound applications in systems with larger number of MCs, the number of transaction queue entries is under-utilized -namely as shallower transaction queues, which provides an opportunity to power saving. In order to address this challenge, we propose the use of transact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Thus, people are facing the need for more efficient systems. It has been found that this can be mitigated by optimizing the number of memory controllers or the on‐chip bandwidth configuration 18–20 . In order to enhance the data processing ability of the chip at a deeper level, more advanced vector architecture processors have been proposed 21,22 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, people are facing the need for more efficient systems. It has been found that this can be mitigated by optimizing the number of memory controllers or the on‐chip bandwidth configuration 18–20 . In order to enhance the data processing ability of the chip at a deeper level, more advanced vector architecture processors have been proposed 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that this can be mitigated by optimizing the number of memory controllers or the on-chip bandwidth configuration. [18][19][20] In order to enhance the data processing ability of the chip at a deeper level, more advanced vector architecture processors have been proposed. 21,22 Vector DSPs for high-speed data processing is one of the typical processors.…”
Section: Introductionmentioning
confidence: 99%